ANALISIS KEBUTUHAN BAHAN AJAR BERMUATAN KETERAMPILAN BERPIKIR TINGKAT TINGGI DI SEKOLAH DASAR - Widya Pratiwi dan Johar Alimuddin (Universitas PGRI Yogyakarta, 2019)
AbstractThe development of science and technology makes various aspects of people's lives change according to development. The education and learning aspect is one that follows these developments. Learning development and innovation continues. The development of teaching materials with high-level thinking skills is one of them. Based on the data obtained, it is needed teaching materials with high-level thinking skills that are simple and easy to use, close to children or in the context around the area where the school is located, and contain material that is sufficient as a source of learning and exam preparation. The results of the analysis are the basis for developing teaching materials with good high-level thinking skills.Keywords: Development, Teaching Materials, Higher Level Thinking